Success of the Cantas Gagal program for ECG243 Soil Mechanics in advancing academic excellence - Keria, Roziah; Ahmad, Azura; Idrus, Juliana; Abdullah, Muhammad Sofian (Unit Penerbitan PKAPP, 2025)
The "Cantas Gagal" program for the ECG243 Soil Mechanics subject was successfully organized to provide additional support to students, with the aim of improving their understanding of critical topics and ensuring their success in the course. A total of 84 students participated in this initiative, which consisted of two sessions held on 29 November 2024 and 24 January 2025. The primary objective of the program was to reduce the failure rate in the subject and provide an opportunity for students to gain deeper insights into challenging topics, thereby boosting their academic performance. The first session, conducted on 29 November 2024, focused on Chapter 1: Physical Properties and Classification of Soil and Chapter 2: Flow of Water Through Soil. The second session, held on 24 January 2025, covered Chapter 3: Shear Strength of Soil and Chapter 4: Soil Compaction and Consolidation. These sessions were guided by a team of dedicated facilitators, including Puan Roziah Keria, Azura Ahmad, Cik Juliana Idrus, and Encik Muhammad Sofian Abdullah, who played a crucial role in delivering interactive and comprehensive sessions. The objective of the program was clear: to provide a platform for students to enhance their understanding of key topics, address any doubts, and better prepare them for upcoming assessments. By focusing on specific chapters and fostering active engagement, the program aimed to reduce academic stress, improve exam performance, and equip students with the knowledge needed to excel in the subject. The program received an excellent response, with over 90% attendance from the 84 students, indicating a strong desire among the students for extra support and guidance. The success of the program was reflected in the results following the test (covering Chapters 1 and 2) and the final exam (covering all the chapters). Notably, 48% of students achieved an A grade, and fewer than 4% failed—a remarkable improvement compared to the previous semester, when 36% of students failed and none received an A grade. One of the most remarkable outcomes of this program was the success of the repeat students. Five students, who had previously failed and were repeating the course (some for the second or third time) managed to pass with excellent results. This not only highlights the effectiveness of the "Cantas Gagal" program in providing support but also demonstrates the positive impact of focused intervention on student success. In conclusion, the "Cantas Gagal" program for ECG243 Soil Mechanics has proven to be a highly effective initiative. It has significantly contributed to improving the academic performance of the students and helped reduce the failure rate in the course. The success of this program exemplifies how targeted academic support can play a pivotal role in helping students overcome challenges and achieve their full potential.